INFLUENCE OF PHYSIOLOGY AND CLIMATE ON δD OF LEAF WAX N-ALKANES FROM C3 AND C4 GRASSES - Smith F.A.; Freeman K.H. (My University, 2006)
We measured hydrogen isotope compositions (δD) of high-molecular-weight n-alkanes (C27-C33) from grasses grown in greenhouses and collected from the US Great Plains. In both cases, n-alkanes from C4 grasses are enriched in D by more than 20? relative to those from C3 grasses. The apparent enrichment factor (°C29-GW) between C29 n-alkane and greenhouse water is -165 ? 12? for C3 grasses and -140 ? 15? for C4 grasses. For samples from the Great Plains, ?D values of C29 n-alkanes range from -280 to -136?, with values for C4 grasses ca. 21? more positive than those for C3 grasses from the same site. Differences in C3 and C4 grass n-alkane ?D values are consistent with the shorter interveinal distance in C4 grass leaves, and greater back-diffusion of enriched water from stomata to veins, than in C3 grass leaves. Great Plains’ grass n-alkane isotopic ratios largely reflect precipitation ?D values. However, the offset or apparent fractionation between n-alkanes and precipitation is not uniform and varies with annual precipitation and relative humidity, suggesting climatic controls on lipid ?D values. The dryer sites exhibit smaller absolute apparent fractionation indicative of D-enrichment of source waters through transpiration and/or soil evaporation. To explore the relationship between climate and n-alkane ?D values, we develop three models. (1) The ’direct analog’ model estimates ?DC29 values simply by applying the apparent enrichment factors, °C29-GW, observed in greenhouse grasses to precipitation ?D values from the Great Plains. (2) The ’leaf-water’ model uses a Craig-Gordon model to estimate transpirational D-enrichment for both greenhouse and field sites. The transpiration-corrected enrichment factors between C29 and bulk leaf-water, °C29-GW, calculated from the greenhouse samples (-181? for C3 and -157? for C4) are applied to estimate ?DC29 values relative to modeled bulk leaf-water ?D values. (3) The ’soil- and leaf-water’ model estimates the combined effects of soil evaporation, modeled by analogy with a flow-through lake, and transpiration on ?DC29 values. Predictions improve with the addition of the explicit consideration of transpiration and soil evaporation, indicating that they are both important processes in determining plant lipid ?D values. D-enrichment caused by these evaporative processes is controlled by relative humidity, suggesting that important climatic information is recorded in leaf wax n-alkane ?D values. Calibration studies such as this one provide a baseline for future studies of plant-water-deuterium systematics and form the foundation for interpretation of plant wax hydrogen isotope ratios as a paleo-aridity proxy. ? 2005 Elsevier Inc. All rights reserved.
Keywords: ALKANE; CLIMATE EFFECT; GEOCHEMISTRY; HYDROGEN ISOTOPE; LEAF; PHYSIOLOGICAL RESPONSE; POACEAE